Curcumin nanocrystals ameliorate ferroptosis of diabetic nephropathy through glutathione peroxidase 4 - Xue, Mengjiao; Tian, Yiwei; Zhang, Hua; Dai, Shijie; Wu, Yangsheng; Jin, Juan; Chen, Jian (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study was to investigate the effect of curcumin nanocrystals (Cur-NCs) on ferroptosis in high-glucose (HG)-induced HK-2 cells and streptozotocin (STZ)-induced diabetic nephropathy model (DN) rats. The purpose is to determine whether Cur NCs can become a promising treatment option for diabetes nephropathy by reducing ferroptosis.MethodsCur-NCs were prepared using microfluidic technology and studied using dynamic light scattering and transmission electron microscopy. HK-2 cells were treated with 30 mM HG to create a renal tubule damage cell model. Then, cell viability was evaluated in HK-2 cells treated with varying concentrations of Cur-NCs (0.23, 0.47, 0.94, 1.87, 3.75, 7.5, 15, and 30 μg/mL) using Cell Counting Kit-8 (CCK-8). Furthermore, in vivo experiments were carried out to investigate the roles of Cur-NCs in STZ-induced DN rats.ResultsThe results showed that HG treatment greatly enhanced the levels of LDH, MDA, Iron, lipid ROS, apoptosis, NCOA4, TFR-1, while decreasing the expression of GSH, GPX4, SLC7A11, and FTH-1. These effects induced by HG could be attenuated by Cur-NCs. Cur-NCs also reduced the HG-induced decrease in cell viability, as well as the increase in lipid ROS and cell apoptosis, however erastin could inhibit their effects. Furthermore, the in vivo results showed that Cur-NCs reduced ferroptosis and inhibited renal damage in DN rats.ConclusionThis study demonstrates that Cur-NCs can significantly attenuate ferroptosis in a STZ-induced renal damage model by recovering GPX4, implying that Cur-NCs may be a promising therapy option for DN.